Pemanfaatan Bunga Kecombrang Sebagai Antioksidan dalam Pembuatan Plastik Film yang Edible - Ari Marlina; Endang Widiastuti; Harita N Chamidy; Ninik Lintang; Avina Vidiati; Pebkristina Halawa (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The era of globalization and current technological developments towards a packaging need, one of which is edible plastic packaging that can be consumed. Antioxidants are compounds that can prevent and repair damage to body cells from free radicals. This study aims to determine the antioxidant activity value (% inhibition) of the Kecombrang flower extract before it becomes edible plastic and after it becomes edible plastic, then the finished edible plastic product characterizes its physical and chemical properties, and applies it to apples. From the test results obtained the best concentration is edible plastic Kecombrang flower extract 25% from the maceration extraction process. The tests carried out obtained % inhibition from the extract by 58% and from edible plastic finished products by 55%, the tensile strength value of 22.11 MPa, the value of water resistance of 18.64%, the detection of FT-IR contains many functional groups of phenols and flavonoids, and the application of apples for 12 hours did not change / the condition of the apples remained fresh.